2010
DOI: 10.1007/s00520-010-0990-y
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and tolerability of transdermal granisetron for the control of chemotherapy-induced nausea and vomiting associated with moderately and highly emetogenic multi-day chemotherapy: a randomized, double-blind, phase III study

Abstract: Purpose A novel transdermal formulation of granisetron (the granisetron transdermal delivery system (GTDS)) has been developed to deliver granisetron continuously over 7 days. This double-blind, phase III, non-inferiority study compared the efficacy and tolerability of the GTDS to daily oral granisetron for the control of chemotherapy-induced nausea and vomiting (CINV). Patients and methods Six hundred forty-one patients were randomized to oral (2 mg/day, 3-5 days) or transdermal granisetron (one GTDS patch, 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 16 publications
0
66
0
Order By: Relevance
“…The emergence of gene array technology identifying the genes coding for the 5-HT 3 and NK 1 receptors may allow clinical correlations and more rational selection of antiemetic regimens for patients. For example, patients with genetic variations in the 5-HT 3B receptor gene might respond differently to antiemetic treatment with the 5HT 3 receptor antagonists [46].…”
Section: Prognostic Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…The emergence of gene array technology identifying the genes coding for the 5-HT 3 and NK 1 receptors may allow clinical correlations and more rational selection of antiemetic regimens for patients. For example, patients with genetic variations in the 5-HT 3B receptor gene might respond differently to antiemetic treatment with the 5HT 3 receptor antagonists [46].…”
Section: Prognostic Factorsmentioning
confidence: 99%
“…tropisetron) depends on cytochrome P-450 2D6 (CYP2D6) genotype, and rapid and ultrarapid metabolisers could be undertreated [23]. Ultrarapid metabolisers could, however, benefit from treatment with a 5-HT 3 antagonist not dependent of the CYP2D6 enzymes (e.g. granisetron).…”
Section: Prognostic Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Information is also available from a pooled population pharmacokinetic analysis, incorporating data from the phase I study (n = 48) and phase II and III studies in cancer patients (n = 793). [28][29][30] Two of these studies are fully published, and the phase II study is available as an abstract. The pharmacokinetics is best described by a two-compartment model with zero-order release from the patch to a buffer compartment and first-order release from the buffer into circulation.…”
Section: Pharmacokinetics Granisetron Metabolism Includesmentioning
confidence: 99%
“…The efficacy and safety of GTS for CINV were evaluated in two randomized, double-blind, double-dummy, parallelgroup, multicenter, premarketing studies: one was a phase II study (n = 171) for single-day MEC, whose results are available from as an abstract 29 and the other was a pivotal 30 The other was an open-label, cross-over, noninferiority phase IV trial that compared the efficacy of GTS with palonosetron for MEC. 32 The results of all three published studies showed noninferiority of GTS.…”
Section: Clinical Studiesmentioning
confidence: 99%